ANALISIS FAKTOR EMOSIONAL DAN RASIONAL DALAM KEPUTUSAN PEMBIAYAAN PERUSAHAAN MELALUI BANK SYARI’AH DI JAWA TENGAH - - Hardiwinoto (Universitas Muhammadiyah Semarang, 2011)
The aim of the research is to analyze empirically about emotional and rational factors that influencingentrepreneurs attitude to taking of decision to funding by syari’ah bank in round of Jawa Tengah. Theaxamination of hypotesis conducted by 192 responders. There are the directors or the company head who hasauthority in making financial decision. The method is used in examination of this hypotesis is linear regresion totest thee independent variables influence to dependent variable.The result of research indicates that result of F count equal to 19.275 at level of significancy 0.000.While each independent variables have own significancy level of emotional (religiousity) significance 0.857accepted at trust boundary 0.10, rational (understanding about financial mechanism of syari’ah banksignificance 0.013 accepted at trust boundary 0.05, and taking decision funding by syari’ah bank significance0.001 accepted at trust boundary 0.001.